Interleukin-3 is a predictive marker for severity and outcome during SARS-CoV-2 infections - Alan Bénard (Nature Portfolio, 2021)
Here, the authors identify interleukin-3 as a predictive marker for severity and outcome of SARS-CoV-2 infection in a multi-center, prospective study and find that patients with severe COVID-19 have reduced circulating plasmacytoid dendritic cell levels compared to non-severe COVID-19 patients.